Budaya Pendidikan Di Flores Timur: Integrasi Nilai Lokal Dalam Sistem Pendidikan Modern - Valentinus Soge Hurint; Maulana Noreng; Siti Inganah (Istifkar: Media Transformasi Pendidikan, 2026)
Educational culture is a fundamental element in shaping the character and identity of students. East Flores, as a region rich in traditional customs, religious values, and social solidarity, has a distinctive and contextual educational culture. However, the development of modern education, which tends to be uniform and oriented towards academic achievement, poses challenges in preserving local values. This study aims to examine the educational culture in East Flores and analyze the urgency of integrating local wisdom into the modern education system. The research method used is a literature study with a descriptive-qualitative approach to scientific literature, education policies, and relevant research results from the last five years. The results of the study show that the educational culture in East Flores emphasizes a balance between intellectual, moral, social, and spiritual aspects. Families, indigenous communities, religious leaders, and schools play an important role in the character education process. The integration of local wisdom into the curriculum and learning is considered capable of increasing the relevance of education and strengthening the identity of students amid the tide of globalization.